Analisis Faktor yang Berhubungan dengan Kejadian Hepatitis B pada Ibu Hamil - Oktobriariani, Rona Riasma; Irma Yanti Simangunsong; BR Tarigan, Intan; Sari, Marlynda Happy Nurmalita (Journal of Midwifery Science: Basic and Applied Research, 2025)
Based on the 2018-2019 Hepatitis and Digestive Tract Infection Information System (SIHEPI), the number of pregnant women tested for hepatitis B was 1,643,204 in 34 provinces. As a result, 30,965 pregnant women were reactive (infected with the hepatitis B virus), and 15,747 newborns from hepatitis B-reactive mothers were given Hepatitis B Immunoglobulin (HBIg). The purpose of this study was to analyze factors related to the incidence of hepatitis B in pregnant women at the Community Health Center in Kelurahan C. This study used a quantitative method with a case-control design where factors related to hepatitis B in pregnant women were tested simultaneously. The sample in this study was 50 people. The results showed a relationship between ANC and the incidence of Hepatitis B (p value 0.040). There was no relationship between education, occupation, family history and history of misuse of unused syringes (p value > 0.05).